2021
DOI: 10.1111/imj.14807
|View full text |Cite
|
Sign up to set email alerts
|

Group A streptococcal bacteraemia at a tertiary hospital in Melbourne: concern of an under‐reported risk group in Australia

Abstract: Background Invasive group A streptococcal (iGAS) infections are increasing worldwide with at‐risk groups being children, pregnant women and the elderly. In 2017, there was a rise in iGAS cases in Victoria, prompting a Chief Health Officer advisory. Aims To describe the characteristics of patients with GAS bacteraemia admitted to a tertiary hospital. To compare at‐risk groups in our population with those identified in the Victorian Government health alert. Methods Retrospective review of patients with GAS bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…The incidence of IE in PWID is known to have increased alongside the opioid epidemic [ 32 ]. An association with IDU and iGAS has also been noted in reports from Australia [ 22 ], the United States [ 24 , 26 ], and Canada [ 27 ], and GAS IE was found to be 10-fold more frequent in PWID with iGAS than those without IDU in the United States [ 26 ]. Among 10 Centers for Disease Control and Prevention Active Bacterial Core surveillance sites, the highest rate of IDU among people with iGAS infections was in 6 Maryland counties surrounding Baltimore City (range, 1.8%–19.3%) [ 26 ].…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…The incidence of IE in PWID is known to have increased alongside the opioid epidemic [ 32 ]. An association with IDU and iGAS has also been noted in reports from Australia [ 22 ], the United States [ 24 , 26 ], and Canada [ 27 ], and GAS IE was found to be 10-fold more frequent in PWID with iGAS than those without IDU in the United States [ 26 ]. Among 10 Centers for Disease Control and Prevention Active Bacterial Core surveillance sites, the highest rate of IDU among people with iGAS infections was in 6 Maryland counties surrounding Baltimore City (range, 1.8%–19.3%) [ 26 ].…”
Section: Discussionsupporting
confidence: 56%
“…Reports from Australia, Europe, and North America have confirmed shifting epidemiology of cases, with increases in incidence and outbreaks of iGAS [ 22–28 ]. Increases in the prevalence of emm1 strains of GAS, associated with invasive streptococcal disease, have also been identified, both coincident with increases in iGAS infection (increase from 5% to 33% of upper respiratory tract isolates over 2 years) [ 25 ] and in periods of stable iGAS incidence [ 28 ].Thus, both increased iGAS cases overall and more invasive GAS species are plausible explanations for the high number of GAS IE seen in this series.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that these risk factors are not well captured by ICD‐10‐AM codes (Supplementary File 1.2), which are loosely defined and do not specifically identify injecting drug use. The potential inadequacy of ICD‐10 codes is highlighted by a single‐centre study of GAS bacteraemia in Melbourne, Victoria from 2014 to 2017 where 18/43 patients (42%) had a history of injecting drug use, 36 whereas our study, which should include all of these cases and covers additional years, only identified 13 cases with drug use coded. A more detailed analysis of prospectively collected data could examine temporal and geographical variation in the prevalence of comorbidities, rates of co‐infection such as influenza, and risk factors such as injecting drug use.…”
Section: Discussionmentioning
confidence: 98%